1990
DOI: 10.1287/orsc.1.2.143
|View full text |Cite
|
Sign up to set email alerts
|

The Bigman Metaphor for Entrepreneurship: A “Library Tale” with Morals on Alternatives for Further Research

Abstract: Melanesian Bigmanship (a meritocratic, enacted career of political-economic leadership) is recounted as an anthropological metaphor for entrepreneurship. This “library tale” has two purposes. The first is a demonstration of conceptual uses of ethnographies for developing grounded theory. Propositions are generated on entrepreneurial orientations and opportunity structures. Opportunities are seen to arise in the creation of linkages between spheres of exchange, or fields in which an object exchanges at differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 71 publications
(12 reference statements)
2
29
0
4
Order By: Relevance
“…In a study of the adoption of Reduced Instruction Set Computer (RISC) technology by computer workstation (Ahuja et al, 2004) Cultural communities (Stewart, 1990) Knowledge heterogeneity (Powell et al, 1996) Factor innovation (Afuah, 2000) Robust designs (Hargadon et al, 2001) Structural holes (Rodan et al, 2004) Market Consumer Political Latent needs (Noda et al, 2001) Fads (Strang et al, 2001) Elite cleavages (Padgett et al, 1993) User innovation (Von Hippel, 1988) User practices (Orlikowski, 2000) Deregulation (Kogut et al, 2002) makers, Afuah (2000) found that leading firms often lost their competitive advantage when new technological opportunities in strategic factor markets rendered the capabilities of key suppliers obsolete. The finding is important because it highlighted the role of strategic factor innovation as a critical technological opportunity for firms operating along a given supply chain.…”
Section: Economic Opportunitiesmentioning
confidence: 99%
“…In a study of the adoption of Reduced Instruction Set Computer (RISC) technology by computer workstation (Ahuja et al, 2004) Cultural communities (Stewart, 1990) Knowledge heterogeneity (Powell et al, 1996) Factor innovation (Afuah, 2000) Robust designs (Hargadon et al, 2001) Structural holes (Rodan et al, 2004) Market Consumer Political Latent needs (Noda et al, 2001) Fads (Strang et al, 2001) Elite cleavages (Padgett et al, 1993) User innovation (Von Hippel, 1988) User practices (Orlikowski, 2000) Deregulation (Kogut et al, 2002) makers, Afuah (2000) found that leading firms often lost their competitive advantage when new technological opportunities in strategic factor markets rendered the capabilities of key suppliers obsolete. The finding is important because it highlighted the role of strategic factor innovation as a critical technological opportunity for firms operating along a given supply chain.…”
Section: Economic Opportunitiesmentioning
confidence: 99%
“…However, as Bloch argued, the moral can also be used for tactical, pragmatic ends (Bloch, 1971;Bennett & Despres, 1998;Song, 1999, pp. 82-88;Stewart, 1990;M. Strathern, 1985).…”
mentioning
confidence: 99%
“…serial monogamy, polygyny) and incorporative practices such as adoption (Stewart, 2010). A related topic is the process of entrepreneurs who dis-embed from kinship obligations at one stage of building their ventures, but re-embed as honored community leaders later on (Hart, 1975;Stewart, 1990).…”
Section: Alertness To Sources Of Solidarity and Conflictmentioning
confidence: 99%